FEW DETERMINATS OF THE AVERAGE AMOUNTS OF MONEY TOURISTS SPEND WHILE VISITING ALBA COUNTY. A REGRESSION MODEL CONSIDERING WHITE'S HETEROSKEDASTICITYCONSISTENT STANDARD ERRORS & THE COVARIANCE AND DIFFERENT WEIGHTS TECHNIQUES. - MUNTEAN, Andreea Cipriana; DOBRA, Iulian Bogdan (Annales Universitatis Apulensis Series Oeconomica; Vol 2 No 18 (2016): Annales Universitatis Apulensis Series Oeconomica, 2016)
This article presents one of the most common tools in making investment decisions - Activity Based Costing (ABC). For this, we focused in the study on the literature review and practice using the ABC method in funding to establish investment decisions. We use for exemplification a project financing with the objective based on upgrading a hotel through complex arrangement works, achieved in order to obtain European funds. The basic information used for the cost-benefit analysis we access using the financial layout related to the funding measure that was desired accessing grants, information found in the financial statements of the company. The accuracy of the method used for this evaluation depends on the accuracy of financial statements provided by the hotel that reflects the work. Thus, our results have allowed us to establish clearly the investment situation, but equally the sustainability and reliability, confirming the need of the hotel analyzed to access grants.